Effects of zingiber officinale on superoxide dismutase, glutathione peroxidase, catalase, glutathione and malondialdehyde content in HepG2 cell line - Abdul Hanif, Harliansyah (2005)
Ginger (Zingiber officinale) is one of the most heavily consumed dietary substances in the world. Some studies have shown that ginger may possess antioxidant and antitumor properties. The objective of this study is to measure activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), glutathione (GSH) and malondialdehyde (MDA) content in human liver cancer cell line (HepG2) and normal liver cell line (WRL-68) treated with Zingiber officinale extract. HepG2 and WRL-68 cell lines were grown in Eagle Minimum Essential Medium of Earle (EMEM) supplemented with 10% fetal calf serum and incubated at 37°C with 5% CO2. Activities of SOD, GPx, CAT, and GSH and MDA contents were measured spectrophotometrically. The results of this study showed that in untreated cultures, high SOD (2 fold higher than normal) activity was found in HepG2 cell line when compared to normal cell line. There were no significant differences in GPx and CAT activities, GSH and MDA contents between the untreated liver cancer and normal cell lines. Ginger extracts at 500 µg/ml, reduced SOD activity significantly by 72.32% in HepG2 cell line when compared to untreated cell lines. Ginger extract also reduced significantly GPx activities by 77.16 %, 87.35 % and 71.05 % in HepG2 cell line at 100, 200 and 500 µg/ml respectively, when compared to untreated culture. Ginger extracts at 200 and 500 µg/ml reduced catalase activities by 41.65 and 67.43 % in HepG2 cell line when compared to untreated culture respectively. Ginger extract had no effect on glutathione and MDA contents in normal (WRL-68) and in liver cancer (HepG2) cell lines at all concentration. This study showed that Zingiber officinale extract may exert its anticancer effect by replacing the function of SOD, GPx and catalase in removing superoxide radicals and hydrogen peroxide that cause oxidative damage to cells.